2019
DOI: 10.1248/bpb.b18-00975
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Platelet Behaviors as Defenders and Guardians: Accumulations in Liver, Lung, and Spleen in Mice

Abstract: Systemic platelet behaviors in experimental animals are often assessed by infusion of isotope-labeled platelets and measuring them under anesthesia. However, such procedures alter, therefore may not reveal, real-life platelet behaviors. 5-Hydroxytryptamine (5HT or serotonin) is present within limited cell-types, including platelets. In our studies, by measuring 5HT as a platelet-marker in non-anesthetized mice, we identified stimulation-and time-dependent accumulations in liver, lung, and/or spleen as importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 167 publications
0
1
0
Order By: Relevance
“…Clinical studies have shown that appropriate platelet supplementation can improve and enhance the anticoagulant function of patients for the purpose of coagulation and hemostasis[ 38 ]. However, repeated blood transfusions have been found to lead to immune tolerance in patients[ 39 ], which subsequently promotes tumor metastasis or recurrence[ 40 ]. In our study, to explore the role of PLTs and their components in the development of HCC, we cocultured PRP, PLTs and PL with HCC cells to observe the effect of PLTs and their components on the biological function of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that appropriate platelet supplementation can improve and enhance the anticoagulant function of patients for the purpose of coagulation and hemostasis[ 38 ]. However, repeated blood transfusions have been found to lead to immune tolerance in patients[ 39 ], which subsequently promotes tumor metastasis or recurrence[ 40 ]. In our study, to explore the role of PLTs and their components in the development of HCC, we cocultured PRP, PLTs and PL with HCC cells to observe the effect of PLTs and their components on the biological function of HCC cells.…”
Section: Discussionmentioning
confidence: 99%